Analysis of plant growth promoting activities of Azotobacter isolates and study of their phenotypic effects on bio-primed rice seeds (Oryza sativa L.) - Aishwarya, P; Lovkush, S; Shweta, M; Mariya, A; Anirudha, C; Jai, P; Ankita, S (Plant Science Today, 2025)
Rising population demands increased agricultural productivity on limited arable land. Excessive use of chemical fertilizers is already affecting the environment so one must turn to environmental friendly solutions of using plant growth promoting and natural nitrogen fixing microbes and analyze their effects on plants. In this study, Azotobacter spp. was isolated from two different geographic areas and their properties were studied. This study investigates the plant growth-promoting (PGP) potential of three Azotobacter strains (M-1, UL-6, A-2.3) and their consortia on rice seeds through bio-priming under in vitro and pot trial conditions. Among 22 isolates tested for phosphate and zinc solubilization, ammonia and IAA production, siderophore formation and salinity tolerance, these strains (M-1, UL-6. A-2.3) performed best. Bio-priming treatments with these strains and a consortium revealed improved germination rates, vigor index (VI), root and shoot development along with chlorophyll content in rice plants. In vitro results showed a 69.06 % germination rate and 426.98 VI for the consortium, while pot trials highlighted UL-6's enhanced root architecture and shoot length with a germination rate of 56.08 % and VI of 375.32 under controlled environmental conditions. However, in vitro results was not always translate to pot trials, suggesting environmental influences, likely due to soil, microbial competition and abiotic factors in non-sterile conditions. The sequence of the best performing strain UL 6 was submitted to NCBI with the accession number PV864958. This study highlights Azotobacter spp. as potential bio-fertilizers for sustainable agriculture and emphasizes the need for optimized bio-priming protocols to ensure consistent plant growth across varying conditions.